Fabrication of air tracks for kinematics and dynamics experiments based on ATMEGA328 microcontroller - Even Triaga; Yulkifli Yulkifli; Yohandri Yohandri (Department of Physics – Universitas Negeri Padang UNP, 2017)
Technological developments and the rapid advancement of science are caused by the increasing needs of human life. One of the disciplines that contributed considerably in the development of technology is physics. Important discoveries related to physics arise in the presence of physics experiments. The most important thing to consider in conducting a physics experiment is the set of experiments. The development of several sets of physics experiments with sensor-based digital systems has been developed, but not yet completely perfect, as in sets of kinematic experiments and dynamics. This study aims to determine the performance specifications and design specifications for the manufacture of Air Track For Kinematics and Atmega328 Microcontroller Based Instructions.This study included into laboratory experimental research. Data collection is done by measuring the quantities of physics contained in the magnitudes in kinematics experiments and dynamics. The measurement technique is a direct and indirect measurement. Direct measurements are made of the travel time of the object. Indirect measurements are made to determine speed, acceleration, and momentum. The data obtained through measurement and analyzed in two ways is statistically and graphically.Based on the results of data analysis can be disclosed some research results. First, this experimental set uses a promini microcontroller that works to process the output of the sensor and converts the sensor output to the desired output. The measurement result view of this experimental set uses the LCD. Sensor used is a photogate sensor that serves to measure the travel time of the object. Second, this experimental set has an average accuracy of 98.82% and an average accuracy of 92.13%. In addition, the phenomenon of perpendicular motion and straight-shifting motion can be well-regulated. Referring to the results of research that has been obtained stated that the developed air track can be used for kinematics experiments and dynamics